Hirudotherapy in the Rehabilitation of Patients with Acute Cerebrovascular Accident - Isakov B.M.; Mamadaliev A.B (Genius Publishing Group, 2022)
Acute disorders of cerebral circulation (ONMC) due to the high prevalence, disability and mortality are one of the most pressing problems of modern medicine. In order to identify the most optimal conservative methods of rehabilitation treatment of small-volume stroke-hematomas, we examined 30 patients with ONMC who received additional treatment with medical leeches during the rehabilitation period. As a comparison group, 32 patients with stroke-hematomas of small volume were taken, whose treatment was carried out in accordance with the algorithms of evidence-based medicine. During the study, in which the general condition and neurological status of the patient were assessed, as well as constant monitoring of blood pressure was carried out, we revealed a noticeable stabilization of vital signs, improvement of the neurological and general condition of patients on the 3rd day of hirudotherapy.
Keywords: Arterial Hypertension; Stroke-Hematoma; Hirudotherapy